Can Research Articles Published in Medical Journals be Used as Expert Evidence in Medical Negligence Cases?—A Cross-Sectional Retrospective Study of Indian Court Judgments - Sethi, Aakash; Shringarpure, Kalpita (Avicenna Journal of Medicine, 2025)
Background The patient party is responsible for producing expert evidence to prove the negligence of a doctor, which becomes difficult due to lack of doctor's willingness to testify against other doctors. Impact factor (IF) is a surrogate to compare the quality of medical journals, which can be divided into low IF (< 10) and high IF (> 10). We aim to analyze various medical negligence cases where the medical journal was cited in court judgments on the parameters like court's verdict, IF of journals cited, compensation awarded, etc.Methods This is a cross-sectional descriptive analysis. Judgments were accessed from www.scconline.com. IF was accessed from Clarivate Analytics 2019 ratings. Judgments having the word “Medical” AND “Negligence” in which either patient or doctor cited any journal data as evidence were included. The ci-square test was used as test of significance.Results Twenty-six judgments met the inclusion criteria, with seven verdicts in favor of doctor (27%). The median IF was 2.455 with the New England Journal of Medicine having the highest IF (70.67). The median compensation awarded was 7.5 lakhs. The verdict of the court (doctor's win or loss) was not dependent on the IF (low IF or High IF) of the journal (chi-square = 0.16, p = 0.68).Conclusion All types of courts handling medical negligence, viz., criminal court, consumer/civil court, writ court, and medical councils, accept medical journal research papers even as the sole evidence in the case of medical negligence. Most of the journals cited were low IF journals.
Keywords: malpractice; negligence; criminal law; medical ethics; standards of care; journal impact factor; practice guideline